Emodin, a Naturally Occurring Anthraquinone Derivative, Ameliorates Dyslipidemia by Activating AMP-Activated Protein Kinase in High-Fat-Diet-Fed Rats. (10th May 2012) - Tzeng, Thing-Fong; Lu, Hung-Jen; Liou, Shorong-Shii; Chang, Chia Ju; Liu, I-Min
Abstract : The aim of this study was to investigate the antiobesity and antihyperlipidaemic effects of emodin on high-fat diet (HFD)-induced obese rats, and on the regulation of the expression of the genes involved in lipid metabolism to elucidate the mechanisms. After being fed HFD for two weeks, Wistar rats were dosed orally with emodin (40 and 80 mg kg −1 ) or pioglitazone (20 mg kg −1 ), once daily for eight weeks. Emodin (80 mg kg −1 per day) displayed similar characteristics to pioglitazone (20 mg kg −1 per day) in reducing body weight gain, plasma lipid levels as well as coronary artery risk index and atherogenic index of HFD-fed rats. Emodin also caused dose related reductions in the hepatic triglyceride and cholesterol contents and lowered hepatic lipid droplets accumulation in HFD-fed rats. Emodin and pioglitazone enhanced the phosphorylation of AMP-activated protein kinase (AMPK) and its primary downstream targeting enzyme, acetyl-CoA carboxylase, up-regulated gene expression of carnitine palmitoyl transferase 1, and down-regulated sterol regulatory element binding protein 1 and fatty acid synthase protein levels in hepatocytes of HFD-fed rats. Our findings suggest emodin could attenuate lipid accumulation by decreasing lipogenesis and increasing mitochondrial fatty acid β -oxidation mediated by activation of the AMPK signaling pathway.